R-Spondin potentiates Wnt/β-catenin signaling through orphan receptors LGR4 and LGR5. - Heinz Ruffner (Public Library of Science (PLoS), 2012)
The Wnt/β-catenin signaling pathbway controls many important biological processes. R-Spondin (RSPO) proteins are a family of secreted molecules that strongly potentiate Wnt/β-catenin signaling, however, the molecular mechanism of RSPO action is not yet fully understood. We performed an unbiased siRNA screen to identify molecules specifically required for RSPO, but not Wnt, induced β-catenin signaling. From this screen, we identified LGR4, then an orphan G protein-coupled receptor (GPCR), as the cognate receptor of RSPO. Depletion of LGR4 completely abolished RSPO-induced β-catenin signaling. The loss of LGR4 could be compensated by overexpression of LGR5, suggesting that LGR4 and LGR5 are functional homologs. We further demonstrated that RSPO binds to the extracellular domain of LGR4 and LGR5, and that overexpression of LGR4 strongly sensitizes cells to RSPO-activated β-catenin signaling. Supporting the physiological significance of RSPO-LGR4 interaction, Lgr4-/- crypt cultures failed to grow in RSPO-containing intestinal crypt culture medium. No coupling between LGR4 and heterotrimeric G proteins could be detected in RSPO-treated cells, suggesting that LGR4 mediates RSPO signaling through a novel mechanism. Identification of LGR4 and its relative LGR5, an adult stem cell marker, as the receptors of RSPO will facilitate the further characterization of these receptor/ligand pairs in regenerative medicine applications.